Differences in foraging strategies and morphology of five warbler species (Parulidae) in a tropical mangrove forest - Barrantes, Gilbert; Sánchez-Quirós, Ana Catalina; Sandoval, Luis (Revista de Biología Tropical, 2025)
Introduction: Understanding the factors underlying the interactions among closely related species continue to be an important issue in ecology and evolution. Warblers have been the group model for studying niche partitioning through interspecific competition, without considering other possible factors. A more recent approach includes species-specific morphologies as an important factor that correlates with habitat (or niche) partitioning. Objective: to compare the foraging strategies of five warbler species (Setophaga p. erithachorides, S. petechia, Protonotaria citrea, Parkesia noveboracensis, and Leothlypis peregrina) in a mangrove forest, and to compare the foraging strategies of S. p. erithachorides, the only resident warbler, between periods (presence vs. absence of migrants). Methods: We collected information on substrates and maneuvers used during foraging for the five warbler species during 39 sampling sessions. Each session consisted of recording information for 9 successive days every two weeks. Results: P. noveboracensis differed extensively from the other species in the foraging substrates and maneuvers. The other species formed a more compact group, but some differences in both, substrates and maneuvers, were detected between S. p. erithachorides and L. peregrina. Differences in forging strategies correlate with differences in the morphology among the five warbles species. The foraging strategy of S. p. erithachorides differed between periods. This warbler used the substrates similarly in both periods, but used other maneuvers or change their frequency when migrants are present. Conclusion: differences in the foraging strategy of five warblers can be attributed to a process of morphological and behavioral adaptation to an adaptive scape that includes differences in microhabitat, and biotic interactions (e.g., predation, prey availability) rather than exclusively to interspecific competition.